Effects of porcine circovirus type 2 and mycoplasma hyopneumoniae vaccination timing and starter diet source on growth performance of nursery pigs - Kane, E. M.; Potter, M. L.; Bergstrom, J. R.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 400 nursery pigs (initially 12.5 lb) were used in a 20-d study to evaluate the effects of varying porcine circovirus type 2 (PCV2) and Mycoplasma hyopneumoniae vaccination timing on growth performance of pigs fed commercial segregated early weaning (SEW) and transition diets from 4 different sources. At weaning (d 0), pigs were blocked by weight and randomly allotted to 1 of 8 treatments. Treatments were arranged in a 2 × 4 factorial on the basis of vaccination timing (0 or 8 d after weaning) and diet source (A, B, C, or D). There were 5 pigs per pen and 10 pens per treatment. Initially, SEW and transition diets were budgeted at 1 and 5 lb/pig, respectively. The SEW and transition diets were formulated to similar Kansas State University specifications but made by different manufacturers. Feeders were emptied on d 8, and a common phase 2 diet was fed for the remainder of the trial. On d 0, 4, 8, and 20, pigs were weighed and feed disappearance was measured to determine ADG, ADFI, and F/G. Diet source influenced (P < 0.001) ADG during the first 4 d of the trial. Pigs fed diet B had increased (P < 0.001) BW (d 4) and ADG (d 0 to 4) compared with pigs fed all other diets, and diet D pigs exhibited increased ADG compared with pigs fed diet C. On d 8, diet source effects remained significant (P ≤ 0.02) for pig weights (d 8) as well as ADG and AD-FI (d 4 to 8 and 0 to 8). Pigs fed diet A had increased (P < 0.01) ADG (d 4 to 8) compared with pigs fed the other 3 diet sources. Pigs fed diets A and B had similar ADFI, but their ADFI (d 4 to 8) was greater (P ≤ 0.02) than that of pigs fed diets C and D. There were no effects of diet source from d 8 to 20. Pigs vaccinated on d 0 had lower (P < 0.01) BW (d 8) and ADG and ADFI (d 4 to 8 and d 0 to 8) than pigs vaccinated on d 8. From d 8 to 20, pigs vaccinated on d 8 had lower (P = 0.05) ADG. Overall (d 0 to 20), diet source and vaccine timing did not influence growth performance, although pigs fed diet C had a numeric decrease (P = 0.06) in ADFI. Nursery pigs in this trial were initially affected by both SEW/transition diet source and vaccination timing, but the influence of these factors lessened with time. Despite the transient nature of these effects, however, data obtained during this trial indicate that nursery pig growth performance is affected by diet source and vaccine timing immediately postweaning, and these factors should be taken into consideration when managing weaning groups.
Keywords: PCV2; Segregated early weaning; Swine; Vaccination